Answer:
√36 = 6
a^2 + b^2 = c^2
6^2 + 6^2 = c^2
36 + 36 = c^2
72 = c^2
√72 = c
2 36
2 18
2 9
3 3
6√2 = c
6√2 = (estimate rounded up, 8.49)
Step-by-step explanation:
paki ayos (*ˊᗜˋ*)ᵗᑋᵃᐢᵏ ᵞᵒᵘ sa pts
Answer: I think its C
Step-by-step explanation:
Answer:
The initial amount a = 1
The growth or decay factor = 0.01025
Step-by-step explanation:
The exponential function.
y = 0.01025^x
The initial amount a = 1
The growth or decay factor = 0.01025
The exponential equation can be rewritten as Y = 1(0.01025)^x
Answer:
4
Step-by-step explanation:
Divide 60 by 15, and you get 4.